Reluctant to reform? A note on risk-loving politicians and bureaucrats - Tobias Thomas; Moritz Hess; Gert G. Wagner (EcoAustria - Institute for Economic Research, 2017)
From a political economy perspective, politicians often fail to implement structural reforms. In this contribution we investigate if the resistance to reform is based on the differences in the risk preferences of voters, politicians, and bureaucrats. Based on three surveys among the German electorate, 175 members of the Federal German Parliament and 106 officials from German ministries, this is not the case. Since both politicians and bureaucrats have a higher risk appetite than the voters, their risk preferences cannot be seen as an explanation for the resistance to structural reform. Hence, it must be caused by other reasons. These could be interventions by veto players, wars of attrition by powerful interest groups, or reform logjams initiated. However, as during times of populist campaigns, the election process can put forth candidates with very high risk appetites, the constitutions of democracies turn out to be rather smart if hazardous actions and measures by political rookies and gamblers are inhibited by checks and balances.
Keywords: D71; D78; H11; H70; P16; Z13; 330; political reforms; political decision-making; principal agent-theory; risk aversion; German; SOEP